2013
DOI: 10.1007/s00394-013-0533-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mineral status are associated with improvements in insulin sensitivity in obese patients following l-arginine supplementation

Abstract: PurposeThe aim of this study is to evaluate the long-term influence of l-arginine intake on mineral concentration in patients with obesity and to assess the changes in lipid serum levels, fat content, and insulin resistance that result.MethodsA randomized double-blind placebo-controlled study was conducted. 88 obese patients were randomly assigned to receive either 9 g of l-arginine or placebo daily, for 6 months. At baseline and after 6 months, selected anthropometrical measurements and blood biochemical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 30 publications
(33 reference statements)
1
31
0
Order By: Relevance
“…However, the change in copper status is directly connected with the change in TAS and TNF alpha level. Other studies support the hypothesis of elevated iron stores, as well as inflammation and oxidative stress, in the development of insulin status disorders [6, 34, 35]. The changes in both iron and copper following the l -arginine supplementation observed in this study may be associated with metabolic relationships between these elements [36, 37].…”
Section: Discussionsupporting
confidence: 84%
“…However, the change in copper status is directly connected with the change in TAS and TNF alpha level. Other studies support the hypothesis of elevated iron stores, as well as inflammation and oxidative stress, in the development of insulin status disorders [6, 34, 35]. The changes in both iron and copper following the l -arginine supplementation observed in this study may be associated with metabolic relationships between these elements [36, 37].…”
Section: Discussionsupporting
confidence: 84%
“…In particular, obese individuals may present with a deficiency of zinc, which aggravates the oxidative stress present in this disease [48,49]. A study conducted by Habib et al [50] in obese individuals found high concentrations of malondialdehyde, a biomarker of lipid peroxidation, when compared with the control group.…”
Section: Chronic Diseasesmentioning
confidence: 99%
“…L-Arginine is involved in several biochemical processes, including polyamine synthesis, ammonia detoxification, immune modulation and secretion of hormones such as glucagon and growth hormone and insulin (14)(15)(16) . What is more, this amino acid produces nitric oxide (NO), a key molecule involved in the regulation of cell metabolism, insulin signalling and secretion, neurotransmission and immune system function (17,18) . It is suggested that L-arginine can be useful in improving lipid profile, due to its potential to increase NO production.…”
mentioning
confidence: 99%
“…Several trials investigated the potential of L-arginine supplementation for the treatment of abnormal lipid profile; however, the results are inconsistent. For instance, some trials report that L-arginine supplementation induced a reduction in circulating concentrations of lipid parameters (20)(21)(22)(23) , while others report no significant effect (18,(24)(25)(26)(27)(28)(29)(30) . Discrepancies in the findings may conceivably be attributed to the differences in study designs, characteristics of study participants, duration and the supplementation dosage applied in the trials.…”
mentioning
confidence: 99%